Analysis of Mechanical and Environmental Effects of Utilizing Waste Glass for the Creation of Sustainable Ultra-High Performance Concrete - Ismaeel A.M.; Usman F.; Hayder G.; Al-Ani Y. (International Information and Engineering Technology Association, 2024)
Typically, waste glass industry contributes to various harmful environmental impacts. Glass manufacturing relies on considerably extreme temperature values. 22 million tons in Europe and 95 million tons of carbon dioxide are generated globally per annum. Meantime, scholars noted that million tons of waste glass produced worldwide yearly could cause elevated levels of water and air pollution due to the accumulation of waste glass in landfills. In this setting, researchers dedicated numerous efforts to create feasible strategies and active solutions to alleviate all these significant numbers. One of those solutions is the waste glass recycling. It is reported that recycling waste glass provides efficient air pollution and water contamination mitigation by roughly 20% and 50%, respectively. One sector that took into account this valuable idea is the concrete industry. Scientists discovered that substituting specific ratios of cement/ sand with waste glass (including 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, and 90%) in concrete could achieve substantial added values in terms of mechanical properties, such as better durability, abrasion resistance, flexural strength, compressive strength, and splitting tensile strength. Few, at the same time, found that adding waste glass into concrete could reduce facilities cooling and heating loads due to the decline in the concretes thermal conductivity. Nonetheless, the available literature lacks adequate proofs associated with this fact. Additionally, different peer-reviewed articles did not address the application of this concept on Ultra-High Performance Concrete (UHPC) but on regular concrete. To bridge this knowledge gap, this manuscript is guided to provide more databases on the influence of cement/ sand replacement with waste glass on concretes thermal characteristics yet paying special attention on UHPC. A comprehensive review is implemented in this context to shed light on these aspects. Based on the thorough review carried out in this article, the outcomes revealed that employing waste glass in concrete and UHPC could attain multiple advantages, like (i) Enhancing variant UHPC and concretes mechanical properties (containing split tensile strength, compressive strength, compaction, durability, flexural strength, bulk density, and shrinkage resistance), (ii) fostering thermal conductivity and thermal resistance, helping make the building of this new concrete mix more energy efficient, (iii) minimizing glass industrys adverse environmental effect, (iii) preserving natural resources, and (iv) reducing the overall budget of UHPC production. However, it is crucial to conduct further experimental and numerical analyses on waste glass replacement with concrete to offer more pieces of evidences and facts of the importance of waste glass replacement in boosting UHPC thermal performance in small and large-scale facilities. 2023 Lavoisier. All rights reserved.